Sassen, S. (2015). Expulsiones. Brutalidad y complejidad en la economía global (Trad. Stella Mastrangelo). Buenos Aires: Katz Editores. 249 páginas - Bertolotti, Florencia (2017)
Fil: Bertolotti, Florencia. Universidad Nacional de Mar del Plata (UNMDP).